How Do Religious Courts Adapt to Digital Justice? Evidence from Family Litigation in Indonesia - M. Doni; Silfia Hanani (Hakamain: Journal of Sharia and Law Studies, 2026)
The digitalization of judicial services has transformed the administration of justice, including the handling of family litigation in Indonesian Religious Courts. This study examines how Religious Courts adapt to digital justice through the implementation of the e-court system and assesses its implications for family law dispute resolution. Employing a socio-legal approach, the research combines normative legal analysis of judicial regulations with empirical data derived from court reports, official documents, and scholarly literature on digital justice. The findings indicate that the adoption of the e-court system has improved procedural efficiency, reduced administrative barriers, expanded access to justice, and enhanced case management in family litigation. However, several challenges persist, including disparities in digital literacy among court users, limitations in technological infrastructure, and unequal access to internet services, particularly in rural areas. These constraints affect the uniform effectiveness of e-court implementation across jurisdictions. The study concludes that Indonesian Religious Courts have demonstrated substantial institutional adaptation to digital justice, although the overall effectiveness of the system depends on continuous technological upgrading, regulatory refinement, and capacity building for users and court officials. Academically, this research contributes to the growing body of scholarship on digital justice by providing empirical evidence from Indonesia’s Religious Court system and offering analytical insights into the relationship between judicial digitalization, access to justice, and family law adjudication in developing legal systems. This transformation underscores the importance of integrating technology with legal reform to ensure equitable, efficient, and transparent judicial services in the digital era in Indonesia and beyond globally comparative context.